Modulation of the structural properties of mesoporous silica nanoparticles to enhance the T1-weighted MR imaging capability. Issue 9 (12th February 2016) - Şen Karaman, Didem; Desai, Diti; Zhang, Jixi; Tadayon, Sina; Unal, Gözde; Teuho, Jarmo; Sarfraz, Jawad; Smått, Jan-Henrik; Gu, Hongchen; Näreoja, Tuomas; Rosenholm, Jessica M.
Abstract : The contrast enchantment for Gd(iii ) incorporated MSN based CAs is investigated by modulating the preparational and structural parameters. Abstract : In this study, we have investigated the contrast enhancement of Gd(iii ) incorporated nanoparticle-based contrast agents (CA) by the modulation of the synthesis and structural parameters of the mesoporous silica nanoparticle (MSN) matrix. In the optimisation process, the structure of the MSN matrix, post-synthesis treatment protocols, as well as the source and incorporation routes of paramagnetic gadolinium centers were considered, with the aim to shorten the T 1 weighted relaxation time. After preliminary evaluation of the prepared MSNs as nanoparticulate T 1 /positive contrast agents based on relaxivity, the structure of the MSN matrix was affirmed as the most decisive property to enhance the r 1 relaxivity value, alongside the incorporation route of paramagnetic Gd(iii ) centers. Based on these findings, the most promising Gd(iii ) incorporated MSN-based CA candidate was further evaluated for its cytocompatibility and intensity enhancement by in vitro phantom MR-imaging of labeled cells. Furthermore, pre-labeled tumors grown on a chick embryo chorioallantoic membrane (CAM) were imaged as an in vivo model on a 3T clinical MRI scanner. Our findings show that the optimized MSN-based CA design enables proper access of water to Gd-centers in the selected MSN matrices, and simultaneously decreases the required amount of Gd(iii ) content per mass when evaluated against the other MSNs. Consequently, the required Gd amount on a per-dose basis is significantly decreased with regard to clinically used Gd-based CAs for T 1 -weighted MR imaging.